Parada cardíaca por fator anestésico em pacientes pediátricos: revisão sistemática com metanálise proporcional e análise de metarregressão - Tiradentes, Teófilo Augusto Araújo [UNESP] (2023)
Study objective: Children have a higher risk of anaesthesia-related cardiac arrest (CA) than adults undergoing surgeries. Studies have demonstrated gaps among countries in the quality of anaesthesia care. The Human Development Index (HDI) ranges from 0 to 1, representing the lowest and highest levels of development, respectively. We examined in mixed paediatric patients the relationship between the global anaesthesia-related CA rates with time and country HDI. Design: This was a systematic review with meta-regression and meta-analysis of observational studies that reported anaesthesia-related CA rates in children. We searched the PubMed/Medline, EMBASE, Scopus, LILACS, and Web of Science databases from inception to July 2022. Setting: 24-hour anaesthesia-related CA rates. Measurements: Anaesthesia-related CA rates were analysed by time and country HDI status in low-HDI (HDI<0.8) versus high-HDI countries (HDI≥0.8) in two periods (pre 2001 versus 2001-2022). Main results: There was no relationship between anaesthesia-related CA rates and time (p=0.82), while the rates were inversely correlated with country HDI (p<0.0001). The rates in children did not change between the periods in either high- or low-HDI countries (p=0.71 and p=0.62, respectively) but were significantly higher in low-HDI than in high HDI countries (9.6 versus 2.0 per 10,000 anaesthetic procedures; p<0.0001) in 2001-2022. The anaesthesia-related CA rates were higher in children <1 year than ≥1 year in high-HDI countries (10.69 versus 1.48 per 10,000 anaesthetic procedures; p<0.0001) and in low-HDI countries (36.02 versus 2.86 per 10,000 anaesthetic procedures; p<0.0001) in2001-2022. Conclusion: Anaesthesia-related CA rate did not decline over the past 60 years. High and alarming anaesthesia-related CA rates among children younger than 1 year in high- and low-HDI countries, respectively, pose challenges for anaesthesiologists. The great differences in the anaesthesia-related CA rates between low- and high-HDI countries in the present century highlight a need to close a widening gap in anaesthesia safety care in these countries.